Assessment of wind energy potential in Chile: A project-based regional wind supply function approach. (October 2016) - Watts, David; Oses, Nicolás; Pérez, Rodrigo
Abstract: Wind energy is now one of the fastest growing renewable energy sources in Chile, making it the second largest market for wind power in Latin America. This paper describes the evolution and the current state of wind power in Chile, presenting the location and performance of all wind farms in Chile. This article also aims to identify the locations of the most cost-effective wind energy potential to be developed in the near future, thus applying a project-based approach. This requires studying each individual wind farm under development or environmental evaluation. This means modeling 70 wind farm projects over the country summing 8510 MW. For each project hourly wind production profiles and histograms are developed, allowing the assessment of variability and spatial and temporal complementarity. The production of neighboring projects injecting their energy in the same transmission bus is aggregated, generating wind production profiles and histograms at transmission level. The Levelized Cost of Electricity of each project is used as a measure of economic feasibility and serves as input to produce wind supply functions for each region. This allows us to identify the most cost-effective wind energy zones for medium-term project development, a valuable input for transmission planners and the regulator. Graphical abstract: Highlights: The production of 70 potential wind farms (8510 MW–26 TWh/yr) is modeled across Chile. Regional wind supply curves developed to assess cost-effective renewable zones. Hourly production profiles of all potential wind farms in Chile are presented. The aggregated effect in profiles and histograms shows benefits of wind integration. Aggregate wind production tends to normalize as more wind farms are integrated.